2018
DOI: 10.4238/gmr16039906
|View full text |Cite
|
Sign up to set email alerts
|

Research Article The effect of acetate Ringer's solution on inflammatory factors and NF-κB signal pathway in the liver of hemorrhagic shock rats

Abstract: To investigate the effect of resuscitation with acetated Ringer's solution during hemorrhagic shock (HS) on inflammatory factors and nuclear factor κB (NF-κB) signaling pathway in liver tissue. Methods: In this study, a rat HS model was established. HS rats received acetated Ringer's solution, lactated Ringer's solution and saline for fluid resuscitation. Inflammatory factors (TNF-α, IL-4 and IL-10) for the evaluation of three kinds of resuscitation mfluid antiinflammatory effect. Expression of proteins in NF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Cannabidiol alleviated the hemorrhagic shock-induced neural apoptosis by the activation of PI3K/AKT signaling pathway (34). In THS rat model, the inactivation of NF-κB p65 protein and TLR4/NF-κB signaling pathway could reverse the expression imbalance of inflammatory mediators and reduce organ damage caused by THS (35). Here, FIG.…”
Section: Discussionmentioning
confidence: 84%
“…Cannabidiol alleviated the hemorrhagic shock-induced neural apoptosis by the activation of PI3K/AKT signaling pathway (34). In THS rat model, the inactivation of NF-κB p65 protein and TLR4/NF-κB signaling pathway could reverse the expression imbalance of inflammatory mediators and reduce organ damage caused by THS (35). Here, FIG.…”
Section: Discussionmentioning
confidence: 84%
“…The inhibition of IκB kinase/NF-κB signaling by BAY11-7082 was shown to improve the proinflammatory response of microvascular endothelial cells in mice with hemorrhagic shock ( 56 ). Previous studies by our team have shown that the inhibition of NF-κB P65 protein and activation of toll like receptor 4 (TLR4)/NF-κB signaling pathway reduced pro-inflammatory cytokines (TNF-α, IL-1, and IL-6) and increased anti-inflammatory cytokines (IL-4 and IL-10) in hemorrhagic shock rats and thus reversed the imbalance of inflammatory mediators and reduced organ damage caused by THS ( 57 , 58 ).…”
Section: Discussionmentioning
confidence: 97%